Inclusion of protein hydrolysate extracted from bycatch in the diet of the Malaysian giant prawn: effects on physiology - Louzã, Ana Carolina [UNESP]; Camargo, Tavani Rocha [UNESP]; Rodrigues, Caio Gomez [UNESP]; Borges, Emanuelle Pereira [UNESP]; Ramaglia, Andressa Cristina [UNESP]; Augusto, Alessandra [UNESP] (Boletim do Instituto de Pesca, 2024)
Bycatch refers to all the animals caught with species of economic interest. These economically unattractive animals are later discarded at sea. Protein hydrolysate with antioxidant potential was extracted by our research group from two main fish species (Paralonchurus brasiliensis and Micropogonias furnieri) of the shrimp fishing bycatch fauna of the São Paulo coast, Brazil. This study tested the inclusion of different concentrations of hydrolysate (0.0, 2.5, 5.0, and 10.0%) in the diet of Macrobrachium rosenbergii. Survival, growth, and physiological processes (ingestion, defecation, hepatosomatic index, O:N ratio, metabolism, and ammonia excretion) were assessed. The inclusion of hydrolysate did not affect crucial parameters for aquaculture, such as survival, growth (about 2% in relation to initial biomass), intake, and mechanisms related to obtaining and using energy (hepatosomatic index and protein as main type of energy substrate oxidized). Metabolism and nitrogen excretion were reduced (~70%) in all treatments with hydrolysate, suggesting lower energy requirements for digestion and absorption of nutrients, as well as the optimization of animal protein use. We recommend the inclusion of 2.5% hydrolysate for future work to test the antioxidant capacity of hydrolysate in M. rosenbergii. This concentration level does not alter important physiological parameters and is cost-effective.
Inclusão de hidrolisado proteico extraído do bycatch na dieta do camarão-gigante-da-malásia: efeitos na fisiologia
Keywords: Accompanying fauna; Bioprospecting marine; Macrobrachium; Shrimp farming